Feasibility of virtual starshot analysis providing submillimeter radiation isocenter accuracy: A long‐term multi‐institutional analysis. Issue 10 (9th September 2019) - Akino, Yuichi; Fujiwara, Masateru; Mizuno, Hirokazu; Shiomi, Hiroya; Kaneko, Akari; Isohashi, Fumiaki; Seo, Yuji; Suzuki, Osamu; Otani, Keisuke; Tamari, Keisuke; Ogawa, Kazuhiko
Abstract: Purpose: We developed a technique to calculate the offset between room lasers and the radiation isocenter using a digital Winston–Lutz (WL) test with a starshot technique. We have performed isocenter localization quality assurance (QA) with submillimeter accuracy for a long period. Here we evaluated the feasibility and accuracy of this virtual starshot (VS) analysis for isocenter localization QA. Methods: A 6‐MV photon beam with a square multileaf collimator field was used to irradiate a WL sphere positioned at the intersection of the room lasers. Images were acquired using an electronic portal imaging device. A four‐field WL test was performed, and the path of each beam was calculated from the offset between the beam and sphere. Virtual starshot analysis was used to analyze the radiation isocenter, which calculates the center of the beam paths by using a least‐squares method, similar to the starshot analysis. Then, eight coplanar and 12 noncoplanar beams were irradiated to evaluate isocenter localization accuracy. Results: Several VS analyses, using different WL spheres, were performed at three institutions, and the calculated accuracies were within 0.1 mm at all institutions. Long‐term analysis showed that the isocenter localization accuracy was appropriately managed with three‐dimensional accuracy within ± 0.5 mm for 90 months after the first laser adjustments. The offset between each beam and the room laser was within 0.6 mm and within 1.0 mm for eight coplanar and 12 noncoplanar beams, respectively, for 90 months. Cone‐beam computed tomography images, acquired after verification beams, showed that the offset between the radiation isocenter and the imaging center was within 0.66 mm for 90 months . The isocenter localization accuracy within 1 mm was kept for long period at other four institutions. Conclusions: Long‐term analysis showed the feasibility of VS analysis for isocenter localization QA, including room laser re‐alignment, noncoplanar irradiation verification, and image guidance accuracy.